Elaboración de compost mediante el método takakura y análisis comparativo de su riqueza nutricional con compost tradicional en el relleno sanitario del cantón Yantzaza, provincia de Zamora Chinchipe - Márquez Carrión, Johanna Marivel (2016)
The preparation of solid organic fertilizers, including compost are of fundamental importance for the improvement of soil fertility. One of them inconvenient in its process of development, is the time for the decomposition of the same, as well as also the ignorance of it wealth nutritional that enable use the same depending on them requirements of them crops. This project is proposed in order to carry out a process of comparison in terms of time, nutritional wealth and cost of manure compost produced in traditional way using the takakura method. The traditional fertilizer was developed in a period of three months, while the takakura method is carried out in 15 days. In what has that view to wealth nutritional, one of them parameters of greater importance is the matter organic, obtaining the method takakura a 46,87% similar to the nitrogen with 49.87%, presenting best results that the compost. With regard to cost, according to the results obtained, the method takakura won lower cost of production. Based on the results achieved, it is recommended to produce compost method traditional, given its production in less time, nutritional richness of higher quality and lower cost of production per bag.